The Practices of Teacher Professional Development Program for English Teachers in Nepal - Kshetree, Arun Kumar (Butwal Campus Journal, 2021)
The Teacher Professional Development (TPD) Program in Nepal is a very much ambitious program aimed at encouraging the teachers for their professional development. This paper aims to study and analyze the situation of implementation of the TPD program to train the English teachers of Nepal in relation to the policy guidelines of the program and to suggest some ways to improve the implementation of the TPD program so that the great resources in the form of investment in training the teachers ultimately result in the improvement of the English language teaching learning situation of Nepal. The results show that the program is very nice and designed perfectly for the Nepalese teachers’ professional development but there are many lacunas in different steps of the implementation of the program which seem to result in the failure of the TPD program in case of ELT teachers training as the transfer of training was found to be very stumpy.